A soft start-up method for DC micro-grid based on improved two-level VSC with DC fault ride-through capability - Wen, Weijie; Lyu, Rui; Li, Botong; Cao, Hong; Yu, Jiali; Li, Bin; Popov, Marjan (Frontiers in Energy Research, 2023)
For the black start-up of DC micro-grids, three-phase charging resistors are required to limit the uncontrollable surge current. The main drawback of this start-up method is the difficulty in determining the appropriate resistance value to achieve a rapid start-up and limit the surge current with the change of grid parameters. To address this problem, this article proposes a soft start-up method for the DC micro-grid based on an improved two-level voltage source converter (VSC). Specifically, an silicon controlled rectifier and anti-parallel diode are added in each up-bridge-arm in the improved VSC. By conducting a dynamic control strategy of the firing angle on the SCRs, the start-up current can always be maintained near a given value to achieve rapid start-up. Moreover, the improved VSC has DC fault ride-through capability. The simulation results based on PSCAD/EMTDC are provided to validate the feasibility of the proposed start-up method.